Strengthening Children's Christian Religious Education to Improve Intellectual Abilities According to Bloom's Taxonomy Domain for Sunday School Children at GKI Eden Anggaduber Biak Timur - Bu’Tu, Dorce; Siahaan, Daniel Syafaat; Banga, Nurhayati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The main problem in this service is the low intellectual abilities of children at the GKI Eden Anggaduber Sunday School in East Biak regarding Christian religious education. The aim of Community Service (PkM) is to strengthen Christian religious education by increasing children's intellectual abilities based on Bloom's Taxonomy. The methods used include lectures, demonstrations and interactive discussions. As a result, children experience improvements in cognitive, affective and psychomotor aspects through a deeper understanding of Bible teachings and their application in everyday life. They demonstrate the ability to memorize, analyze, and apply Christian values. In conclusion, this program succeeded in strengthening Christian religious education while improving children's intellectual abilities in accordance with the principles of Bloom's Taxonomy, creating a strong foundation for sustainable spiritual and intellectual growth at GKI Eden Anggaduber.